PUDRING SEBAGAI PRODUK UNGGULAN WIRAUSAHA MERDEKA: STRATEGI INOVASI DAN PEMASARAN - Jonathan Dharma Nalendra; Awin Mulyati (Cahaya Ilmu Bangsa, 2025)
The Wirausaha Merdeka program provides opportunities for students to create and develop innovation-based businesses. One proposed flagship product is Pudring, a donut-shaped pudding that combines unique design with delightful taste. This study aims to analyze innovation, marketing, and sustainability strategies in developing Pudring as a business opportunity. Using a qualitative descriptive approach, the research identifies key factors influencing the success of Pudring, including product design, the use of high-quality ingredients, and the utilization of digital media for promotion. The results show that Pudring’s innovative shape and flavor successfully attract consumers, while social media-based marketing strategies effectively expand market reach. Furthermore, the application of sustainability principles through the use of eco-friendly materials and recyclable packaging adds value to the product. With a combination of innovation, marketing, and sustainability, Pudring has great potential to thrive as a flagship product in the culinary industry. This article aims to serve as a reference for young entrepreneurs in creating creative and sustainable businesses.